Uncertainty and economic performance in the West African Monetary Zone (WAMZ): A fixed effect panel threshold approach - Ngozi Eunice Egbuna; Maimuna John-Sowe; Dauda Mohammed; Hissan Abubakari; Eric L. Sambolah; Kormay Adams (West African Monetary Institute (WAMI), 2020)
Concerns about the impact of the general global uncertainty on economic performance have dominated academic debate in the aftermath of the Global Financial Crisis leading to huge body of empirical studies on ways of measuring and quantifying countries uncertainty and its impact on GDP, investment flows and employment. The paper utilized the Global Uncertainty Index - a metric developed from the quarterly Economic Intelligence Unit reports from 1996 to 2018. The paper adopted fixed-effect threshold model to determine whether uncertainty does affect economic performance in the WAMZ and to test for the presence of at least a threshold effects that would justify the consideration of nonlinear regression in estimating the nexus between uncertainty and economic performance in the WAMZ. The overall results confirmed the presence of both single and double threshold effects thus justifying the acceptance of a nonlinear panel regression model against a linear one. The paper brought to the fore, the negative consequences of ignoring the role of uncertainty when member countries are making growth projections. The paper recommends policy actions that may reduce uncertainty, boost investment, and pare-up economic activities in the Zone.
Keywords: C13; C33; C58; 330; Uncertainty; Growth; West African Monetary Zone; Global Uncertainty Index; Panel Threshold